2019
DOI: 10.3390/jcm8020265
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Flow Restriction Resistance Exercise for Older Adults with Knee Osteoarthritis: A Pilot Randomized Clinical Trial

Abstract: In a pilot randomized clinical trial, participants aged ≥60 years (n = 35) with physical limitations and symptomatic knee osteoarthritis (OA) were randomized to 12 weeks of lower-body low-load resistance training with blood-flow restriction (BFR) or moderate-intensity resistance training (MIRT) to evaluate changes in muscle strength, pain, and physical function. Four exercises were performed three times per week to volitional fatigue using 20% and 60% of one repetition maximum (1RM). Study outcomes included kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
125
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(132 citation statements)
references
References 52 publications
(59 reference statements)
0
125
0
2
Order By: Relevance
“…Skeletal muscle function will be assessed via unilateral isokinetic strength of knee extensors of the dominant limb via a dynamometer as previously published (47,48). Indices of angiogenesis will be evaluated via the collection and analysis of percutaneous skeletal muscle biopsies.…”
Section: Exploratory Outcomesmentioning
confidence: 99%
“…Skeletal muscle function will be assessed via unilateral isokinetic strength of knee extensors of the dominant limb via a dynamometer as previously published (47,48). Indices of angiogenesis will be evaluated via the collection and analysis of percutaneous skeletal muscle biopsies.…”
Section: Exploratory Outcomesmentioning
confidence: 99%
“…[ 3 ] According to statistics, the incidence of KOA among the elderly is relatively high, and approximately 30% to 50% of the elderly over 60 are affected by KOA. [ 4 ] Due to its progressive and chronic symptoms, KOA not only reduces the quality of life of the affected individuals, but also requires a large amount of healthcare resources and involves considerable social treatment costs, and these needs will inevitably increase with the aging of the population. [ 5 , 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] Currently, the incidence of KOA in the elderly is quite high, and it is reported that 30% to 50% of the elderly population more than 60 years of age suffer from KOA. [ 4 ] With the coming of the aging of the world population, KOA has become a concerning public health problem that not only brings an increasing social and economic burden but also threatens the physical and mental health of patients as well as reduces the quality of life of the elderly. [ 5 , 6 ] Meanwhile, studies have shown that besides joint discomfort, patients with knee osteoarthritis are more likely to have poor sleep and feel anxiety and depression compared with healthy people.…”
Section: Introductionmentioning
confidence: 99%